2019
DOI: 10.1021/acschembio.9b00704
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small Molecule Chimeras That Recruit AhR E3 Ligase to Target Proteins

Abstract: Targeted protein degradation using chimeric small molecules such as proteolysis-targeting chimeras (PROTACs) and specific and nongenetic inhibitors of apoptosis protein [IAP]-dependent protein erasers (SNIPERs) is an emerging modality in drug discovery. Here, we expand the repertoire of E3 ligases capable of ubiquitylating target proteins using this system. By incorporating β-naphthoflavone (β-NF) as a ligand, we developed a novel class of chimeric molecules that recruit the arylhydrocarbon receptor (AhR) E3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 55 publications
1
65
0
Order By: Relevance
“…Interestingly, the 1-induced significant reduction of CRABP-2, but not of CRABP-1, was also observed in SH-SY5Y cells, which do not express AhR ( Figure S1 and S2). Similar results were also obtained by the treatment of the ITE-ATRA [16], in which an alternative AhR ligand was used ( Figure S3). The ligand-bound AhR forms a CUL4B-based E3 ligase complex [17].…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Interestingly, the 1-induced significant reduction of CRABP-2, but not of CRABP-1, was also observed in SH-SY5Y cells, which do not express AhR ( Figure S1 and S2). Similar results were also obtained by the treatment of the ITE-ATRA [16], in which an alternative AhR ligand was used ( Figure S3). The ligand-bound AhR forms a CUL4B-based E3 ligase complex [17].…”
Section: Introductionsupporting
confidence: 80%
“…We previously developed the chimeric compound β-NF-JQ1 that is directed against bromodomain-containing (BRD) proteins using β-NF or (+)-JQ1 as an AhR or BRD ligand, respectively. β-NF-JQ1 induced the AhR-dependent degradation of BRD proteins in MCF-7 cells expressing AhR [16]. However, the β-NF-JQ1-induced reduction of BRD3, but not of BRD2 or BRD4, was also observed in SH-SY5Y cells, which do not express AhR ( Figure S7), suggesting that BRD3 is also degraded by the AhR-independent mechanism.…”
Section: Evaluation Of Protein Degradation Activitymentioning
confidence: 93%
See 2 more Smart Citations
“…65 Degraders recruiting IAP were named specific and nongenetic IAP-dependent protein erasers (SNIPERs). [66][67][68][69][70][71][72][73][74][75][76] Later, von Hippel-Lindau ligands used for PROTAC design were identified by the Ciulli laboratory. [77][78][79] Concurrently, it was found that the E3 cereblon (CRBN) was the molecular target of the immunomodulatory drugs (IMiDs), such as thalidomide, pomalidomide, and lenalidomide.…”
Section: Introductionmentioning
confidence: 99%